2008
DOI: 10.4314/ajtcam.v4i3.31223
|View full text |Cite
|
Sign up to set email alerts
|

Effect Of Walnut Leaf, Coriander And Pomegranate On Blood Glucose And Histopathology Of Pancreas Of Alloxan Induced Diabetic Rats

Abstract: Mechanism of most of herbal used for diabetes mellitus treatment has not been well defined. This study was performed to investigate hypoglycemic effect of walnut leaf (Juglans regia L.), coriander leaf (Coriandrum sativum L.) or pomegranate seed (Punica granatum L.), and their possible role on pancreatic tissue. Diabetes mellitus was induced in 20 adult male Sprague Dawley rats and the animals were divided into four groups; three of them fed a diet supplemented with about15 gram (60 g/ kg body weight /day) of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
69
0
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(82 citation statements)
references
References 16 publications
4
69
0
4
Order By: Relevance
“…There is a need to continue to explore the relationship between free radicals, diabetes, and its complications, and to elucidate the mechanisms by which increased oxidative stress accelerates the development of diabetic complications, in an effort to expand treatment options. Some plants and trace elements may be proven the candidates to bring about the promising and desirable results to circumvent the day-by-day spreading menace of diabetes mellitus [10]. Coriander has been documented as a traditional While comparing the FBS levels of group C (Diabetic rats treated with coriander only) with the group A (Control), 19% increase in FBS has been noted that was not at par with the control group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is a need to continue to explore the relationship between free radicals, diabetes, and its complications, and to elucidate the mechanisms by which increased oxidative stress accelerates the development of diabetic complications, in an effort to expand treatment options. Some plants and trace elements may be proven the candidates to bring about the promising and desirable results to circumvent the day-by-day spreading menace of diabetes mellitus [10]. Coriander has been documented as a traditional While comparing the FBS levels of group C (Diabetic rats treated with coriander only) with the group A (Control), 19% increase in FBS has been noted that was not at par with the control group.…”
Section: Discussionmentioning
confidence: 99%
“…insulin, Biguanides and Sulphonyl Ureas, to bring about the promising and desirable results to circumvent the day-by-day spreading menace of diabetes mellitus with minimum or no side effects [9]. In herbal antidiabetic studies, along with a list of herbs, coriander (Coriandrum Sativum) [10] has been reported to be hypoglycemic. A study on mice found that coriander extract had both insulin-releasing and insulin-like activity [11].…”
Section: Introductionmentioning
confidence: 99%
“…Kelompok (KI) diberi pelarut aloksan berupa NaCl 0,9%, sedangkan kelompok (KII) diberikan aloksan dengan dosis 150 mg/kg bobot badan. Semua perlakuan diberikan secara intraperitoneal sebanyak 0,5 ml pada masingmasing tikus tersebut (Jelodar et al, 2007). Setelah satu minggu pasca pemberian aloksan, tikus putih KII dilakukan pemeriksaan gula darah puasa untuk memastikan tikus putih menderita DM dengan menggunakan easy touch ® .…”
Section: Prosedur Penelitianunclassified
“…Pengukuran kadar gula darah dilakukan pada hari ketujuh setelah induksi aloksan. Kisaran diabetogenik aloksan untuk memperlihatkan aktivitas toksisitas antara 180-200 mg/dl (Jelodar et al, 2007), namun untuk ditetapkan dabetes dan digunakan sebagai hewan uji diambil yang kadar glukosa darah ≥ 200 mg/dl.…”
Section: E T O D Eunclassified